BAGAIMANA NASIONALISME DAN PERSEPSI TENTANG PAJAK MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DI PEDESAAN DAN PERKOTAAN (PBB-P2) - Asmawi Darmawan; Edi Mulyadi; Jarnawi Afgani Dahlan (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2020)
The purpose of this study is to determine the relationship between independent variables and the dependent variable, which is used as the independent variable in the study, namely nationalism (X1) and perceptions of tax (X2) while the dependent variable is taxpayer compliance (Y). The way to solve the problem is to find out the relationship between nationalism and taxpayer compliance and perceptions of taxes with taxpayer compliance and the concurrent relationship between nationalism and perceptions about taxpayer compliance using quantitative methods. The chosen research respondents were the Rural and Urban Land and Building taxpayers in each Kelurahan in the Larangan City District of Tangerang. The results showed a significant relationship between nationalism and taxpayer compliance, and a significant relationship between perceptions of tax and taxpayer compliance and simultaneously nationalism and the perception of taxpayers had a significant relationship with taxpayer compliance. From the results of this study, a further study is needed to improve taxpayer compliance in paying Rural and Urban Land and Building Taxes related to factors other than nationalism and perceptions of taxes, namely taxpayer compliance in registering, taxpayer compliance to deposit SPPT, compliance in calculation and payment of outstanding taxes and compliance with payments and arrears.